Exploring communication supports for children with visual impairment and blindness: A case study - Kristen Abrahams; Dellicia de Vos; Armand Bam; Harsha Kathard (African Journal of Disability)
Background: Early communication supports are essential for development, learning and later employment. For children with visual impairments and blindness (VI and B), we argue that communication and its supports need to be considered outside of the normative ableist framework to best facilitate development.